Relationship of knob morphometric analysis with production performance and meat quality in Yangzhou goose (Anser cygnoides) - Zhang, Yang; Xu, Xinlei; Ji, Wangyang; Qi, Shangzong; Bao, Qiang; Cao, Zhi; Liu, Wei; Zhang, Yong; Zhang, Yu; Xu, Qi; Chen, Guohong (Frontiers in Physiology, 2023)
The development of the knob in Chinese geese (Anser cygnodies) is an outcome of extensive and prolonged selection and breeding. The knob serves not only as a visual indicator of sexual maturity in geese but also holds significance as a crucial packaging trait that attracts attention of consumers attentions, who tend to distinctly prefer geese with larger knobs. Consequently, investigating the formation of the knob holds practical value, as it will help achieving external traits aligned with consumers’ preferences. To understand the relationship between knob size, production efficiency, and meat quality in Yangzhou geese, we examined histological and anatomical characteristics in 500- and 120-day-old geese with large and small knobs. Notably, knob size had a pronounced impact on key anatomical and structural parameters, such as chest depth, leg muscle water-binding capacity, and insoluble collagen composition in Yangzhou geese (p < 0.05). In addition, we measured testosterone and estrogen levels in male and female geese, respectively, as well as growth hormone, and found that birds of both sexes with a large knob had higher sex and growth hormone levels in the body. This study established a fundamental theoretical basis for advancing the enhancement of goose knob traits.